Les dimensions multiples de l’engagement ludique - Olivier Caïra (Sciences du Jeu, 2018)
M. Csíkszentmihályi’s theory of flow provides a popular definition of engagement in games. It is of great interest for game studies, particularly by its emphasis on autotelic activities and by its consideration of challenge, learning and pleasure. However, flow cannot provide all the keys to engagement in games. G. Calleja’s model seems more suited for the study of contemporary games. The six dimensions he explores reveal gaming as an intrinsically complex and non optimal behaviour. His distinction between macro- and micro-engagement sheds light on neglected forms of our relationship to games, which manifest themselves outside gaming sessions. The MÉDIAL model (Moteur [Engine], Épreuve [Test], Diégèse [Diegesis], Intrigue [Plot], Autrui [Others] and Ludologie [Ludology]) takes up Calleja’s multidimensional approach, adding two ambitions to it. Firstly, under- and over-engagement must appear as socially problematic behaviours. Secondly, reflexivity must not be treated as a form of detachment but as a genuine dimension of engagement in games. MÉDIAL allows mapping games and gamers within a complex space and without prejudging the legitimacy of each form of engagement.